State of Innovation in Suicide Intervention Research with Military Populations. Issue 3 (28th October 2014) - Conner, Kenneth R.; Simons, Kelsey
<x xml:space="preserve">Abstract</x> A systematic search was performed to identify active, externally funded randomized controlled trials (RCTs) that target suicidal ideation or behavior as a primary or secondary outcome among U.S. military service members, guard–reservists, and veterans. Twenty‐three studies were identified, most funded by the U.S. Department of Defense or U.S. Department of Veterans Affairs. Several innovations were identified based on departures from or modernizations of usual practices and included the targeting of suicide deaths or attempts as primary outcome, delivery of interventions through technology and/or outside clinical settings, and examinations of rarely studied treatments.